Speech act-based legitimisation in selected inaugural speeches of British Prime Ministers - Buczowski, Maciej; Strukowska, Marta Eliza (Scripta Neophilologica Posnaniensia, 2022)
This paper offers insight into discursive patterns of the two most recent BritishPrime Ministers’ inaugural speeches from an anthropological pragmatics perspective. The paper employed speech act theory in conjunction with a qualitatively centered critical discourse analysis study to unveil messages within the illocutionary communicative acts in the context of public political speeches. It is argued that both speeches are inherently embedded within threat-based rhetoric whose persuasive effect follows from a predominant use of the pathos and ethos appeals. Advancing the concept of speech acts as a tool for establishing pragma-discursive patterns, this paper demonstrates that generating fear in public discourse is essentially strategic and goal-oriented practice. Most importantly, the strategies used by Rishi Sunak rely heavily on his use of promises and statements, reflecting patterns of legitimisation through building a credibility schema and proximising the frame of fear mongering. Liz Truss on the other hand, develops slightly different narrative patterns, drawing mainly upon promises that help enact ‘collective leadership’ in the times of threat and a socio-economic crisis.